Hypertension and Headache in the Setting of Vertebral and Carotid Fibromuscular Dysplasia - Omar Almaadawy; Lisa Harvin; Kalyan Paudel; Christopher Haas (Annals of Internal Medicine: Clinical Cases)
A 98-year-old woman presented in the context of headache and was found to have evidence of a beaded appearance of the bilateral carotid and vertebral arteries. Fibromuscular dysplasia of the carotid and vertebral arteries is rare but may present with symptoms of headache, dizziness, transient ischemic attack, or stroke. Management of symptomatic patients focuses on the use of antihypertensive drugs and secondary prevention with antiplatelet agents. Surgical intervention is referred for those cases that are nonresponsive to the aforementioned treatments.